Optimization of Community Participation in the Complete Systematic Land Registration Program (Ptsl) in Paren Village, Mayong District, Jepara Regency - Putri, Ainaya Qalbina; Darmadi, Nanang Sri (Jurnal Konstatering, 2025)
Abstract. Complete Systematic Land Registration, hereinafter abbreviated as PTSL, is a Land Registration activity for the first time which is carried out simultaneously for all Land Registration objects throughout the territory of the Republic of Indonesia in one village/sub-district area or other name of the same level, which includes the collection and determination of the truth of physical data and legal data regarding one or several Land Registration objects for the purposes of registration. The approach method in this study is qualitative. This type of research includes empirical legal research. The types of data in this study are primary data and secondary data obtained through interviews and literature studies. The analysis in this study is descriptive. The results of the study concluded 1) The participation of the Paren Village community in the PTSL program is still relatively poor. This is evidenced by the target certificate data of 800 but community participation is only 539 2) The main problems faced in Paren Village are the lack of community participation in participating in the PTSL program, land that has not been divided or has not been divided, so that the community cannot participate in the certification process, lack of community understanding of the benefits and objectives of PTSL, costs that are considered burdensome, lack of effective socialization from the village government and BPN to provide an understanding to the community about the importance of PTSL.Keywords: Community; Participation; Problems; Registration; Village.